Single-Layered Flexible Dual Transmissive Rasorbers With Dual/Triple Absorption Bands for Conformal Applications - Mehran Manzoor Zargar (IEEE, 2021)
This article presents flexible frequency selective surface (FSS) based rasorbers exhibiting dual/triple absorption bands along with dual-band transmission. The proposed rasorbers are designed by combining the individual designs of dual-/triple-band resonant absorber and dual bandpass FSS on the two sides of a flexible substrate. At the absorption frequencies, the bandpass FSS acts as reflective metallic ground. The proposed FSS based rasorbers are flexible, single-layer structures having a thickness of $0.005λ _{0}$ at the lowest absorption frequency and can serve as suitable candidates for the much practical conformal applications. The working of the proposed rasorbers is analyzed using an equivalent circuit model. Further, an optimum range at each absorption frequency is determined by studying the parametric effects on the proposed design. Prototypes consisting of $17×25$ unit cells are fabricated and experimental validation is achieved. The performance of the rasorbers is also studied by bending their fabricated prototypes with 120°, 150°, and 180° degrees of curvatures.